Analysis of High-Order Thinking Skills of High School Students in Solving Problems Related to Temperature and Heat - Wakhidyah, Sasti Handayani; Supriadi, Bambang; Anggraeni, Firdha Kusuma Ayu (Department of Physics Education, Universitas Mataram, 2023)
Higher Order Thinking Skills are abilities that students must have in facing the challenges of the industrial revolution era 4.0 because higher-order thinking skills are complex thinking processes that involve conscious activities that will later be taken an action. The purpose of this study was to analyze higher-order thinking skills of 11th grades in senior high school in Jember. The method used is a qualitative descriptive method with data collection techniques for temperature and heat test result based on higher-order thinking skills and interviews. The result of this study, students have the ability to analyze 48.5%, evaluate 41%, and creation 39.5%. The conclusion of the research is students are in the moderate category in analyze and evaluate aspect, low category in the create aspect, it means students able to formulate the completion stage but are less able to combine information to produce the correct answer.